Screening potential local seed species for hydroseeding of post-coal mining land multilayering revegetation - Anshari, Muhammad Fadhil; Fernandes, Adji Achmad Rinaldo; Leksono, Amin Setyo; Arisoesilaningsih, Endang (Journal of Degraded and Mining Lands Management, 2023)
This study aimed to screen some potential local seed grains for hydroseeding and describe their characteristics based on the literature review and a year of hydroseeding application. This study used six species/variants of Poaceae (Coix lacryma-jobi, Eleusine indica, Setaria italica (brown, black, and red), Sorghum timorense, S. bicolor, Themeda arundinaceae), five species of Leguminosae (Adenanthera pavonina, Cajanus cajan, Sesbania grandiflora, S. sesban, Indigofera sp.), a species of Cyperaceae (Cyperus javanicus), Sapindaceae (Sapindus rarak), Rhamnaceae (Ziziphus jujuba), and Moringaceae (Moringa oleifera). A seed germination test was held using soil media placed in 5 pots per species until 15 days after sowing (DAS). Characters were scored, and data were statistically analyzed. A field record of one-year hydroseeding applied on 6 m x 6 m post-coal mining land plot was presented. Some data such as pH H2O, pH KCl, conductivity, and soil organic carbon among hydroseeding areas, unrevegetated areas, and reference sites were observed. Results showed that there were 13 of 17 species could variably germinate. The fastest germination time was recorded for S. timorense, S. bicolor, red S. italica, C. cajan, and S. grandiflora, while the highest germination rate (â‰¥50%) was black S. italica (80%), brown S. italica (58%) and S. bicolor (50%). The annual black and brown S. italica, S. bicolor, and S. timorense were highly recommended to be used in hydroseeding. The perennial C. cajan, Indigofera sp., S. sesban, and T. arundinaceae were also potential to be added into a hydroseeding slurry to improve pioneer vegetation multilayering structure and diversity.